Тoponyms in the Kazakh and Turkish languages (Journal of Oriental Studies, 2017)
The article deals with morphological structure of place names in Russianand Kazakh languages. In Kazakh and Russian languages, the compositionand structure of names is a complex process. Morphological structureof place names is closely connected with the rules of word formation of thelanguage. Word-building means not only the formation of new words butalso a semantic change.In the process of creating place names in Russian and Kazakh languagesare used all the ways of word formation. Place names the same as thederivative words are formed through three main ways of word formation.